Optimasi Pemilihan Pekerja Kasar Perumahan Pada PT. Yaguna Bangun Pratama Menggunakan Metode Analytical Hierarchy Process dan Promethee - Panji Prasuci Saputra; Marji Marji; Yuita Arum Sari (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Technological advancement as a vessel for the interests of various jobs that occurred in this era, demands competent human resources. Human resources have a very important role in the interaction of capital factors, materials, methods, and machinery. One example of human resources is the building course workers. Hence, this journal examines rough building workers in PT. Yaguna Bangun Pratama. This journal tries to selectbuilding course workers who do not meet the criteria of the company (PT Yaguna Bangun Pratama). Based on these problems, it takes an application that can process the data into a system optimization of rough-labor election. The analytical hierarchy process (AHP) dan Promethee method was chosen because it was able to rank the best alternative from a number of alternatives. The test used is bu usingthe changes of 5 types of preference in the Promethee method. The results of the usual preference type and quasi preference type resulted in a match rate of 80%, whereas the linear preferences type and the linear preferences type with unlimited areas resulted in a match rate of 60%, and the type of level preference resulted in a match rate of 40%. In other words, the greater the percentage of the suitability of the system with the expert, the better the system is